Papers of Harold Clive Newman - Newman, Harold Clive, 1896-1983. (1910)
A collection of photographs, correspondence, citations and some newsclippings; an autobiography in typescript entitled: "Harold Clive Newman, C.B.E: this is your life, revised edition, June 1979".
Manuscript reference no. : MS 6479.
Former Commonwealth Auditor-General (Who's Who in Australia, 1980).
Keywords: Newman, Harold Clive, -- 1896-1983 -- Archives; Public officers -- Archives; Civil service -- Australia; Public servants